The Philosophy of Language Acquisition in Stephen Krashen's Theory based Multiple Intelligences Classroom - Suci Ramadhanti Febriani; Wildana Wargadinata; Zainul Arifin (Postgraduate of IAIN Metro Lampung Indonesia, 2021)
Language acquisition and language learning among scientists tend to be different. This is based on the fact that the language acquisition process is supported unconsciously and is limited to a certain time. Meanwhile, the language learning process can be done consciously and is not limited by time. Through these two arguments, according to Stephen Krashen the acquisition process has certain characteristics. He believes that language acquisition can be obtained in adults. Based on this information, the researcher wants to describe and analyze the philosophy that encourages Stephen Krashen to develop a theory of language acquisition through classroom management based on Multiple Intelligences. This study used a qualitative research design with a case study method at SD Plus Al-Kaustar Malang, Indonesia. Data collection included observation, interview and documentation study through an analysis technique consisting of three steps; data collection, reduction and conclusion. The results showed that the philosophical background built in the theory of Stephen Krashen based on Multiple Intelligences is a empiricism philosopgy. This is known through the process of language acquisition which is formed through an adequate language environment carried out by the sensory experiences of students with the help of their cognitive thinking processes. These findings indicate that language acquisition can be done through a good environmental design even though it has passed the age limit for first language acquisition.